Facebook as an alternative public sphere: online discussions of bond notes in Zimbabwe - Mandoreba, Angellah (Midlands State University, 2018)
The research examines social media as an alternative public sphere. Special attention is paid to Facebook, a social networking site, which opened up online spaces for public dialogue on Bond notes, a surrogate currency in Zimbabwe, in 2016. Using The Herald Facebook Page as a case study, the research drew insights from a number of scholars on the notion of public sphere, among them Habermas and Fraser in order to study the extent and manner in which Zimbabweans’ use of Facebook to deliberate the introduction of Bond notes constructed a digital public sphere. It was observed that Facebook conforms to several Habermas ideals of a public sphere. The online platform provides a conducive and favorable environment for public discussions because it is fashioned with a number of features capable of facilitating debate. While the online public sphere has limitations, these mainly differed from those of the physical public sphere in the extent to which they manifest. Further researches on social media as an alternative public sphere in Zimbabwe may be conducted with special attention to other social media sites like WhatsApp and Twitter.